2008
DOI: 10.1111/j.1399-5618.2007.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its association with insight, adverse effects of medication and use of atypical antipsychotics in patients with bipolar disorder and schizophrenia in remission

Abstract: The results of the present study indicate that subjects with BD are dissatisfied with their QOL, even when they are in a remitted state. Clinicians must consider the negative influences of insight and adverse effects of medication on QOL of patients with BD and schizophrenia in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
38
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 45 publications
12
38
2
1
Order By: Relevance
“…Patients assess their satisfaction for each item over the past 2 weeks on a 5-point scale (from 1 = ''very dissatisfied'' to 5 = ''very satisfied'') [33,34]. The WHOQOL-BREF has been a widely used SQOL instrument in schizophrenia research [35,36], and use of the WHOQOL-BREF allows our findings to be compared with those of previous studies.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Patients assess their satisfaction for each item over the past 2 weeks on a 5-point scale (from 1 = ''very dissatisfied'' to 5 = ''very satisfied'') [33,34]. The WHOQOL-BREF has been a widely used SQOL instrument in schizophrenia research [35,36], and use of the WHOQOL-BREF allows our findings to be compared with those of previous studies.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…The mean EQ-VAS score at 3 years for remitters was similar to that reported for the general population (König et al, 2009). Previous reports have found that quality of life in patients with schizophrenia in symptomatic remission is lower than in healthy individuals (Yen et al, 2008). However, the study by Yen et al (2008) did not use a representative sample of general population subjects and did not specify for how long the patients included had been in remission.…”
mentioning
confidence: 98%
“…For this, the regression model can be adjusted for other factors known to impact on quality of life and to be associated with remission (e.g. age, gender and medication) (Haro et al, 2006;Yen et al, 2008;Potkin et al, 2009). Finally, we have described the relationship between functional remission and quality of life.…”
mentioning
confidence: 99%
“…The subjective quality of life (SQoL) is one of the most important outcomes among the impaired health-related outcomes for people with schizophrenia, with growing interest for healthcare providers (Lin et al, 2012). Many studies (Carpenter & Buchanan, 1994;Hegarty et al, 1994;Hooley, 2010;Yen et al, 2008) have shown that an individual's SQoL, including physical and psychological aspects, is impaired in people with a mental illness such as schizophrenia. Mental health professionals could improve the health and wellbeing of people with schizophrenia by finding ways to improve their SQoL.…”
mentioning
confidence: 99%